Microbial Toxins: Types, Mechanisms of Action, and Pathogenic Significance - Mayada Abdullah Shehan; Sara Imad Hajwal (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Microbial toxins are critical virulence factors that contribute to disease by directly damaging host cells or modulating immune responses. Specific Background: Existing classifications, including exotoxins and endotoxins, often fail to integrate structural characteristics with mechanisms of entry, activation, and signaling pathways, particularly in relation to lipopolysaccharide recognition and mycotoxin-related public health concerns. Knowledge Gap: A cohesive framework linking toxin structure, delivery mechanisms, and immunopathological outcomes remains insufficiently developed in current literature. Aims: This review aims to establish an integrated classification of microbial toxins and to elucidate their mechanisms of action across molecular, cellular, and immunological levels. Results: The study identifies key toxin categories, including A–B toxins, membrane-disrupting toxins, superantigens, lipopolysaccharides, and mycotoxins, and outlines core mechanistic principles such as delivery, cellular selectivity, post-entry activation, and signal amplification, leading to inflammation and cell death. It also highlights the role of host variability and microbiota interactions in shaping toxic responses. Novelty: The review proposes a multidimensional framework combining structural, functional, and immunological perspectives to better interpret toxin behavior and disease patterns. Implications: These findings support the development of targeted interventions, including toxin-neutralizing therapies, improved vaccine design, and standardized research approaches for clinical and laboratory applications. Highlights:• Integrated framework links toxin structure with delivery and activation processes• Functional classification connects mechanisms to specific pathological outcomes• Host variability and microbiota interactions shape toxin-related disease patterns Keywords: Microbial Toxins, Exotoxins, Endotoxin, Lipopolysaccharide, Mycotoxins